2022
DOI: 10.3389/fonc.2022.974885
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of soluble Neuropilin-1 in ovarian cancer patients and its association with its circulating ligands of the HGF/c-MET axis

Abstract: BackgroundNeuropilin (NRP) is a transmembrane protein, which has been shown to be a pro-angiogenic mediator and implicated as a potential driver of cancer progression. NRP-1 up-regulation in ovarian cancer tissue predicts poor prognosis. However, the clinical relevance of the soluble form of NRP-1 (sNRP-1) as a circulating biomarker in ovarian cancer patients is unknown.Methods/patients cohortsNRP-1 levels were quantified in a cohort of 88 clinically documented ovarian cancer patients by a commercially availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Our finding may reflect the summation of comorbidities in which NRP-1 has contributing pathologic roles. Several studies have assessed systemic and tissue-level NRP-1 and associated it with mortality, but only in participants with diagnosed cancer to assess prognosis [ 4 , 5 ]. None to our knowledge have evaluated all-cause mortality in a broader population without a prevalent cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding may reflect the summation of comorbidities in which NRP-1 has contributing pathologic roles. Several studies have assessed systemic and tissue-level NRP-1 and associated it with mortality, but only in participants with diagnosed cancer to assess prognosis [ 4 , 5 ]. None to our knowledge have evaluated all-cause mortality in a broader population without a prevalent cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…NRP-1 was initially identified relating to signal transduction, cell migration, angiogenesis, and vascular permeability [ 3 ]. In pathologic states, NRP-1 is most studied in malignancy, where increased plasma and tissue expression is associated with worse outcomes across numerous cancers [ 4 , 5 ]. NRP-1 also has key immunologic functions involving T-cell maturation, upregulation on activated CD4 + T cells, and an immunoregulatory and cell migration role with T-regulatory (Treg) cells and macrophages [ 6 , 7 ].…”
mentioning
confidence: 99%
“…A family gene, NRP-2 (human chromosome 2q33.3), encoding a novel member of the family protein neuropilin-2 (NRP-2) that contains 931 amino acids with 104 kDa, was identified as a high-affinity receptor for the Semaphorins ( 2 ). Previous studies revealed that NRP family proteins exert multiple functions as co-receptors for vascular endothelial growth factor (VEGF) ( 3 ), transforming growth factor beta (TGF-β) ( 4 ), hepatocyte growth factor ( 5 ), fibroblast growth factor (FGF) ( 6 ), and Semaphorin 3 (SEMA3) ( 7 ). NRP family proteins are involved in the interaction with multiple ligand receptors, thus NRP family proteins may be involved in cancer occurrence and development and might serve as therapeutic targets for gastric cancer ( 8 ), glioma ( 9 ), endometrial cancer ( 10 ), bladder cancer ( 11 ), thyroid cancer ( 12 ), breast cancer ( 13 ), gallbladder cancer ( 14 ), colorectal cancer ( 15 ), and pancreatic adenocarcinoma (PDAC) ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of the total soluble NRP-1 has become available using a novel sandwich ELISA [31]. However, the extent of sNRP-1 functions remains incompletely understood [17,[32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed as a potential therapeutic target [35][36][37][38][39]. NRP-1 has been extensively researched as a prognostic biomarker and therapeutic target in cancer and leukemia [17,19,24,25,28,33,34]. Interestingly, NRP-1 has also been found to be expressed in liver cells and appears to be upregulated in various liver-related pathologies [39][40][41].…”
Section: Introductionmentioning
confidence: 99%